Intact polar lipid fatty acids carbon isotopic composition of sediment core YC22_MR_7 off Herschel island (Yukon Coast 2022) - Ruben, Manuel Jannis; Mollenhauer, Gesine (In: Ruben, MJ; Mollenhauer, G (2024): Biogeochemical data of sediment cores of Herschel island (Yukon Coast 2022) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.965379, 2024)
In July 2022 within the framework of an Alfred-Wegener-Institute-managed expedition and the Nunataryuk project, sediment core YC22_MR_7 was taken off the coast of Herschel Island, Canada, using a hand corer. Data sets were obtained to investigate carbon feedback from the sediments to the water column and atmosphere, using DIC concentrations and isotopic values. The local sediments are supplied primarily by organic carbon previously stored in adjacent permafrost soils (biomarker and bulk data), which erode and redeposit quickly (age model) on the ocean floor. Intact polar lipid fatty acids were extracted from the sediments, purified, and 14C analysis was performed as described in Ruben et al. (2023). The 13C isotopy was determined with GC-IRMS (Elvert et al., 2003).